Greywater reuse - Assessment of the health risk induced by Legionella pneumophila. (15th November 2017) - Blanky, Marina; Sharaby, Yehonatan; Rodríguez-Martínez, Sara; Halpern, Malka; Friedler, Eran
Abstract: Greywater (GW), domestic wastewater excluding the streams generated by toilets and kitchens, can serve as an alternative water source. The main options for GW reuse are toilet flushing and garden irrigation, both generating aerosols. These may transmit inhalable pathogens like Legionella and present a potential health risk. This study quantified the health risk that may arise from inhalation of Legionella- contaminated aerosols due to non-potable GW reuse. Data on Legionella concentrations in potable water and GW was collected. Then, Quantitative Microbial Risk Assessment (QMRA) was performed for two possible exposure scenarios: garden irrigation and toilet flushing. This was performed while considering Legionella seasonality. In order to determine the safety of GW reuse regarding Legionella transmission, the obtained results were compared with estimated tolerable risk levels of infection and of disease. Both limits were expressed as Disability-Adjusted Life Years index (DALY) being 10 −4 and 10 −5, respectively. The QMRA revealed that the annual risk associated with reuse of treated and chlorinated GW for garden irrigation and toilet flushing was not significantly higher than the risk associated with using potable water for the same two purposes. In all studied scenarios, the health risk stemming from reusing treated and chlorinated GW was acceptable regarding Legionella infection. In contrast, reuse of untreated or treated but unchlorinated GW should not be practiced, as these are associated with significantly higher health risks. Graphical abstract: Highlights: Greywater (GW) are domestic wastewater excluding streams from toilets and kitchens. Quantitative Microbial Risk Assessment (QMRA) was performed for Legionella in GW. The QMRA for treated and chlorinated GW was not significantly higher than the for potable water. Health risk stemming from treated GW is acceptable regarding Legionella infection.